L’approche latino-américaine de l’économie populaire, les inégalités et la pauvreté - Isabelle Hillenkamp (Revue de la Régulation)
This article analyses the evolution of the policies and theories in development economics since the 1950’s. It shows the reasons of their decline at the beginning of the 1980’s and situates the approach of the popular economy which emerges in Latin America in this context. Based on the case of Bolivia, it illustrates the interest of this socioeconomic and non-evolutionist approach of the practices of production, exchange and financing of the popular sectors for a renewed analysis of inequalities and poverty. To this end, two observation scales are successively adopted: a micro-scale observation of the institutional environment and functioning of the organizations of the popular economy and the analysis of the macro-institutional framework in which these organizations are embedded.